Obligaciones legales de las asociaciones cooperativas bancos comunales en Venezuela - Coromoto Aguilar González, Herleny (Gestión Joven, 2009)
n Venezuela se promulga la Ley Especial de Los Consejos Comunales en el año 2006. El Consejo Comunal está constituido por tres órganos: Órgano Ejecutivo, Unidad de Gestión Financiera, y Unidad de Contraloría Social. La Unidad de Gestión Financiera o Banco Comunal adquirirá la figura jurídica de cooperativa, por consiguiente el presente trabajo tiene por objeto analizar los deberes formales que debe cumplir el Banco Comunal: 1. Inscribirse en los registros correspondientes; 2. Llevar Libros Legales; 3. Presentar Declaración Informativa de ISLR; 4. Practicar retención de ISLR; 5. Emitir factura de conformidad con lo establecido en la regulación venezolana.Venezuela promulgated the Special Law of the Communal Councils in 2006. The Communal Council is constituted by three agencies: Executive agency, Financial Management Unit, and Social comptroller Unit. The Financial Management Unit or Communal Bank will acquire the legal figure of a cooperative, therefore the present paper intends to analyze the formal duties established in the Venezuelan tax laws, that the Communal Bank must fulfil: 1. To register in the corresponding registration system; 2. Keep the accountancy Books required by tax laws; 3. To file an informative income tax return; 4. To practice income tax withholding; 5. To emit invoice in accordance with Venezuelan tax regulations.